A new species of the genus, Turanogryllus Tarbinsky, 1940 from India with re-description of T. pakistanus with data on acoustic signals (Grylloidea: Gryllidae: Gryllinae) - Monaal; Meena, Ashok Kumar; Gulati, Harsh; Swaminathan, Rajamani; Jaiswara, Ranjana (Zootaxa, 2025)
The genus Turanogryllus of the family Gryllidae was described by Tarbinsky, 1940 based on its unique morphological features. A total of 38 valid species are known from across the world; of these, 19 species have been reported from the Indian Subcontinent. We describe a new species, Turanogryllus pandajhirensis sp. nov. with detailed characters of males and females and redescribe Turanogryllus pakistanus Ghouri & Ahmad, 1959 by emending characters. We provide high resolution images of the species. In addition, we document acoustic signal features of both species.